2021
DOI: 10.4236/jbm.2021.910009
|View full text |Cite
|
Sign up to set email alerts
|

Improving Clinical Laboratory Quality through Reduction of Tests’ Turnaround Time in Democratic Republic of the Congo: Key Strategies

Abstract: In Democratic Republic of the Congo (DRC), the laboratory TAT is significantly very long and do not comply with either international standards or the suggestions of customers. However, there is neither a national nor a local strategy to improve the laboratory TAT. The aim of the present study is to develop practical management strategies to shorten clinical laboratory tests' TAT. This was a qualitative study conducted in Kinshasa. Focus groups and Lean tools were used respectively to generate a wide range of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…Anderson et al similarly used VSM to identify 22 minutes of NVA in their phlebotomy area which could be optimised by a series of interventions like automated phone system, additional phlebotomy station, patient wait time display, designated courier pick-up points, and task redistribution. 23 Alain et al 24 found 62% of NVA in their laboratory workflow right from patient reception, sample assemblage to result reporting which could be entirely eliminated using lean methods. TC Inal et al 8 found that the preanalytical process in the reception area was improved by eliminating 3 h and 22.5 min of nonvalue-adding work.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Anderson et al similarly used VSM to identify 22 minutes of NVA in their phlebotomy area which could be optimised by a series of interventions like automated phone system, additional phlebotomy station, patient wait time display, designated courier pick-up points, and task redistribution. 23 Alain et al 24 found 62% of NVA in their laboratory workflow right from patient reception, sample assemblage to result reporting which could be entirely eliminated using lean methods. TC Inal et al 8 found that the preanalytical process in the reception area was improved by eliminating 3 h and 22.5 min of nonvalue-adding work.…”
Section: Discussionmentioning
confidence: 99%
“…Letelier at al 10 used the lean management principles to reduce the TAT for glucose and haematocrit by using redesigning their preanalytic process. Alain et al 24 used Value stream mapping to improve the process flow within their laboratory and reduced their average TAT from 503 minutes to 191 minutes. 24 In the study by TC Inal et al Egypt reported compliance to timeliness to inpatient reporting was much lower at 35%, reaching 60% after improvement using DMAIC methodology, which is improvement by 25%.…”
Section: Turn-around Timementioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, microvascular damage in patients with type 2 diabetes is often detected late due to delays in clinical laboratory trials (An et al, 2021;Gedebjerg et al, 2018). Some of the factors contributing to this delay include a lack of awareness of the importance of regular health checkups and the high cost of laboratory tests (Alain et al, 2021;Gebreyes et al, 2020). Research has also shown that inflammation can be recognized through increased levels of leukocytes in the blood (Kizilgul et al, 2018;Milosevic & Panin, 2019).…”
Section: Introductionmentioning
confidence: 99%